Toward Molecular Quantum-Dot Cellular Automata: A Scanning Tunnelling Microscopy investigation - TORSNEY, SAMUEL (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2018)
In this work we used scanning tunnelling microscopy and scanning tunnelling spectroscopy to investigate the adsorption, assembly and electronic properties of two different ferrocene-decorated porphyrins on both metallic and insulating substrates. All experiments were carried out in ultra-high vacuum and at low-temperature (77 K). These functional molecules were specifically designed for molecular quantum-dot cellular automata, a computational paradigm where charge configurations are used to represent binary states. The first molecule investigated has consists of four amido-ferrocene groups coupled to a tetraphenylporphyrin (TPP) core. The TPP part of the molecule was found to dominate its adsorption properties on the close-packed faces of gold and copper, where different self-assembly motifs were observed. The electronic properties of these arrays were examined and it was found that the frontier orbitals were well-localised to different parts of the molecule. A serious challenge was in finding a thin insulating film on metal system which was compatible with electrospray deposition. We found that NaCl is modified upon exposure to electrospray, and we propose that other ionic films will be similarly modified, which will be of interest to the wider surface science community. The high coverage Cu2N-Cu(100) surface was found to be the best candidate examined, however its usefulness was limited by the small terrace sizes. We found that the strain-relieving trenches template the molecular self-assembly on this surface. We also investigated a brominated diferrocenyl-porphyrin. This molecule was designed to facilitate polymerisation, which was unsuccessful on Au(111) in the temperature range afforded by the thermolabile functional groups. However, the monomer was found to self-assemble on both Au(111) and Cu2N-Cu(100), and upon investigating the electronic properties on the respective surfaces, we found conformational dependence of molecular orbital energies and coupling of an electronic state across a molecular ribbon.
APPROVED
Keywords: Scanning Tunnelling Spectroscopy; Scanning Tunnelling Microscopy; Quantum-dot Cellular Automata; Ferrocene-functionalised Porphyrins